(untitled) (Kronika Bydgoska, 2010)
The beginnings of the activity of farmers from Bydgoszcz Voivodeship were recorded as early as November 1980, when the Presidium of the Voivodeship Founding Committee of the Independent Self-Goveming Trade Union NSZZ “Solidarność Chłopska” (Peasant Solidarity) was established. In the next months, Bydgoszcz was the venue of the National Conference of “Solidarność Chłopska”, a convention of the National Negotiating Committee of NSZZ “Solidarność Chłopska”, a convention of the Temporary Negotiating Committee of the Farmers’ Trade Union, during which the National Negotiating Committee of the Individual Farmers’ Independent Self-Goveming Trade Union NSZZ "Solidarność” (Solidarity) was established, with its head office in Bydgoszcz. Additionally, it was in Bydgoszcz on February 8, 1981 that the national gathering of individual farmers was organised. Another important event was one month’s sit-down strike of peasants at the head office of the Voivodeship Committee of the United Peasant Party in late March and early April 1981, which finally resulted in signing an agreement with the govem- ment, under which the Individual Farmers Independent Self-Goveming Trade Union NSZZ “S” was registered.